Detection of ESR1 Mutations Based on Liquid Biopsy in Estrogen Receptor-Positive Metastatic Breast Cancer: Clinical Impacts and Prospects - Liao, Hao; Huang, Wenfa; Pei, Wendi; Li, Huiping (Frontiers in Oncology, 2020)
Endocrine therapy is the main treatment option for estrogen receptor-positive (ER+) breast cancer (BC). Compared with other clinical subtypes, ER+ BC patients usually have a more favorable prognosis. However, almost all ER+ BC patients develop endocrine resistance and disease progression eventually. A large number of studies based on liquid biopsy suggest that ESR1 mutations may play a key role in this process. For patients with ER+ metastatic BC (MBC), ESR1 is an important prognostic factor and may associate with the resistance to endocrine therapy, like aromatase inhibitors. The advances of sequencing technologies allow us to conduct longitudinal monitoring of disease and unveil the clinical implications of each ESR1 sub-clone in ER+ MBC. Moreover, since the ESR1-related endocrine resistance has not been fully addressed by existing agents, more potent cornerstone drugs should be developed as soon as possible. Herein, we reviewed the recent progress of detecting ESR1 mutations based on liquid biopsy and different sequencing technologies in ER+ MBC and discussed its clinical impacts and prospects.